Performance of subcarrier-OCDMA system with complementary subtraction detection technique. - Sahbudin, Ratna Kalos Zakiah; Abdullah, M. K.; Mokhtar, Makhfudzah; Ahmad Anas, Siti Barirah; Hitam, Salasiah (World Academy of Science, Engineering and Technology (WASET), 2011)
A subcarrier - spectral amplitude coding optical code division multiple access system using the Khazani-Syed code with Complementary subtraction detection technique is proposed. The proposed system has been analyzed by taking into account the effects of phase-induced intensity noise, shot noise, thermal noise and intermodulation distortion noise. The performance of the system has been compared with the spectral amplitude coding optical code division multiple access system using the Hadamard code and the Modified Quadratic Congruence code. The analysis shows that the proposed system can eliminate the multiple access interference using the Complementary subtraction detection technique, and hence improve the overall system performance.